Successful unroofing of anomalous aortic origin of the left coronary artery with intramural course in patient with near syncope - Firdaus, Achmad Jauhar; Handari, Saskia Dyah; Prasetya, Indra; Tjahjono, Cholid Tri (Universitas Brawijaya, 2025)
BACKGROUND: Left Anomalous Coronary Artery from the Opposite Sinus of Valsalva (L-ACAOS) refers to a congenital heart defect in which the left coronary artery originates from the right coronary sinus of Valsalva. This condition may increase the risk of sudden cardiac death (SCD), especially for those participating in intense physical exertion. This paper presents a case of a malignant type L-ACAOS in a young male who underwent successful surgical correction. CASE: A 35-year-old male without any known coronary artery disease risk factors presents with angina and near syncope while competing in a marathon run. He regularly participates in endurance sporting events without any complaints. However, in the last two years, he has begun to complain of angina during exertion. The ECG examination showed early repolarization in the inferior and lateral leads with no significant lab abnormalities. This led to coronary computed tomography angiography (CCTA), which revealed that the left coronary artery originates from the right coronary sinus and runs between the pulmonary trunk and ascending aorta, indicating a malignant-type anomalous coronary artery. He then undergoes a surgical correction with unroofing of the left main coronary artery and relocate the LMCA orifice to the left sinus. The procedure proceeded uneventfully with satisfactory results. CONCLUSION: Anomalous coronary arteries are concerning because they are associated with increased risks of SCD. The intramural course is associated with a higher risk of SCD due to stenosis caused by lateral compression that leads to ischemia and potentially fatal arrhythmias, making early detection and intervention critical.